One Health Approach Reveals the Absence of Methicillin-Resistant Staphylococcus aureus in Autochthonous Cattle and Their Environments - Correia, Susana; Silva, Vanessa; García-Díez, Juan; Teixeira, Paula; Pimenta, Kevin; Pereira, José E.; Oliveira, Soraia; Rocha, Jaqueline; Manaia, Célia M.; Igrejas, Gilberto; Poeta, Patrícia (Frontiers in Microbiology, 2019)
Antimicrobial resistance represents one of the greatest challenges of the twenty-first century, and it is globally recognized that addressing this problem requires a concerted One Health approach involving humans, animals, and the environment. Methicillin-resistant Staphylococcus aureus (MRSA) currently represents a global burden; it is resistant to almost all beta-lactams and some MRSA strains are highly multiresistant. S. aureus infection in cattle results in major economic losses in the food industry. Moreover, cases of livestock-associated MRSA strains responsible for invasive life-threatening infections have been reported among human patients in contact with infected or colonized animals. The autochthonous Maronesa cattle breed is a threatened rustic traditional Portuguese breed of mountain cattle of high importance for the Vila Real region. It has been used for centuries as motive power in all kinds of agricultural work and also for meat production, which is its current dominant use and the main source of economic value, being the Maronesa meat commercialized with PDO - Protected Designation of Origin. This study aimed to determine the prevalence and transmission of MRSA in cattle of the Maronesa breed, through a concerted One Health approach comprising human, water, and soil samples of the animals’ handlers and environments. In a total of 195, 63, 40, and 43 cattle, human, water, and soil samples screened in selective ORSAB media supplemented with 2 mg/L oxacillin; only one human sample harbored a MRSA isolate which was ascribed to spa-type t9413 and to ST30, one of the most common genetic lineages associated with community-acquired MRSA. Considering the increasing reports of MRSA isolation from cattle and handlers in Europe, the absence of this major human and animal pathogen in Maronesa cattle and their production systems represents a serendipitous result, valuing this important autochthonous breed. To our knowledge, this is the first study to determine MRSA prevalence and transmission in Maronesa cattle. Through a concerted One Health approach, this study revealed that the Maronesa cattle and their surrounding environments do not represent reservoirs for Methicillin-resistant Staphylococcus aureus.